When math meet culture: Exploring ethnomathematics in red mosque’s design - Nabilla Namira Permata Putri; Yoppy Wahyu Purnomo (Jurnal Elemen, 2025)
Mathematics can be found in cultural aspects. Moreover, Indonesia has a variety of cultures that can be explored and used as mathematics learning resources. Existing mathematics learning has yet to integrate cultural elements that are close to students. The aim of this study is to examine the findings of geometric objects and mathematics activities in the Moekhlas Sidik Red Mosque. The research method used was an ethnographic study and data collection techniques in the form of observations, documentation, and interviews. The obtained data were analyzed using an interactive model: data reduction, data presentation, data interpretation, and conclusion. This study found that the geometric objects include 2D shapes, 3D shapes, and geometric transformations. The 2D shapes observed are triangles, trapeziums, squares, rectangles, rhombuses, and semicircles. The 3D shapes that can be observed are rectangular prisms. Geometric transformation is the use of the principles of translation, reflection, and rotation. The mathematical activities that can be explored include creating tile patterns, finding the purpose of tile patterns, and drawing 2D shapes using geometric transformation principles. In addition, the existence of the Moekhlas Sidik Mosque provides socioeconomic value that has an impact on the surrounding community.